Meningkatkan Pelayanan Melalui Public Relations yang Harmonis dan Humanis di Masa Pandemi COVID-19 - Siantari Rihartono (PARAHITA : Jurnal Pengabdian kepada Masyarakat, 2021)
Public Relations is a strategic function in management that communicates to generate understanding and acceptance from the public. Some principles of a harmonious relationship during the Pandemic: Honest communication for credibility. Openness and consistency of steps taken to gain the confidence of others. Fair steps to gain reciprocity and goodwill. Continuous two-way communication to prevent estrangement and to build relationships. Evaluation and research of the environment to determine the steps or adjustments to be made. Improved service based on harmonious relationships can be done by an employee at the faculty in serving students so that long-term relationships are established. The service improvement can be done with the principles of a harmonious relationship by using the following steps needed for social harmony. The strength possessed by Public Relations is the basis of great optimism for its success in carrying out its duties, namely being able to build great trust from the public.